Qualitative study on single parents managing their work and non-work roles with the use of external support and coping strategies. - Chong, Lena Mei Tian. (2008)
The aim of this paper is to explore the types of support that single parents will depend on to manage their work and non-work roles. This paper begins with an overview of past research studies on the topic of single parents and how they manage their different roles. This is a qualitative research conducted using interviews based on the critical incident technique. Participants were four female single parents who are divorced or in the process of divorce obtained from a family service center. Each of the participants has at least one child in their custody. With grounded theory, the data obtained were being analyzed using two coding methods, which are open coding and axial coding respectively. Responding to the interview conducted, results showed that the single parents relied on various forms of external support. More interestingly, the results revealed that the single parents relied more on internal support. Some intervening conditions were also being discovered. This paper ends with discussions on the limitations of this research, its implications and areas for further studies in future.